COVID-19 IN CHILDREN WITH DOWN SYNDROME - CASE SERIES - Ivanovska, Julija; Nestorov, Hristijan; Popova, Gorica; Chakalarovska, Irena; Petlichkovska, Sandra; Boskovska, Katerina (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Down syndrome (DS) is the most common genetic disease and presents with cognitive impairment, cardiac and gastrointestinal abnormalities, increased risk of hematological malignancy and several autoimmune conditions in addition to other miscellaneous clinical conditions. Children with DS are at increased risk for more severe presentations of COVID-19 because of that efforts should be made to ensure the comprehensive and early detection of COVID-19 in this population. The aim of these case reports is to show if the comorbidities that these children have, including cardiovascular anomalies, obesity, and/or obstructive sleep apnoea [7,8], were risk factors for more severe form of COVID-19. Case number 1:In September 2021 , a 14 year old girl with Down Sy was admitted to our hospital due to fever, cough, myalgia and shortness of breath . She tested positive for SARS-CoV-2. The patient had foramen ovale apertum after birth with spontaneous closure, and recurrent respiratory infections. At admission she was afebrile, pale, with frequent productive cough, dyspnÐµic with low Oxygen saturation, auscultatory with bilateral pneumonic finding. She had chest X-ray with bilateral pericardial areas of consolidation (multifocal opacities) in peripheral and in the lower lobes, and elevated IL6. She was treated for 20 days with antibiotics, broncholidators, Remdesivir, LMWH, and oxygen therapy. There was slow withdrawal of the the auscultatory lung finding. Case number 2: In March 2022 , a 5 year old boy with Down Sy was admitted to our hospital due to fever, rhinorrhea, vomiting , dehydratation , cough, tested positive for SARS-CoV-2 . At admission he was subfebrile, pale with moderate dehydration with dry buccal mucous membranes, tachycardia, sunken eyes ,hypotonic auscultatory on the lungs with pneumonic finding. Chest X-ray showed patchy areas of consolidation in right pericardial area. He was treated with intravenous (IV) fluid, antibiotic and inhaled bronchodilator. There was withdrawal of the auscultatory lung finding during the 10 days of hospital stay. Case number 3: In March 2022, a 6 year old boy with Down Sy was admitted to our hospital due to fever, laryngitis with hoarseness, dry cough, dehydratation, He had Type 1 insulin-dependent, diabetes mellitus (Type 1 DM) diagnosed at age of 5. He was febrile, pale , dehydrated with hoarseness, laryngeal cough auscultatory vesicular breathing with bubbly crackles. Blood gases (ABG) was suggestive of compensatory metabolic acidosis , urine with ketonuria and glycosuria. Chest X-ray: patchy areas of consolidation in right lower lung zones. Treatment was started with IV fluid, topic corticosteroids and the regular insulin therapy. There was withdrawal of the symptoms during the 8 days of hospital stay. Conclusion: Children with Down Sy are always a high risk group for more severe and prolonged course of disease, which are partially attributed to defects of the immune system. Key words: children, Covid - 19, Down syndrom